Over the counter sale of abortion pills - time to act now - Sharma, Ritu; Gupta, Mamta; Sharma, Shakti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Government of India has approved abortion pill for termination of early pregnancy. But over the counter availability of this drug instead has earned a bad name for this miracle drug. The aim of this study was to find out the incidence of over the counter availability of abortion pills, the outcome associated with this practice and what cost society has ultimately to pay for this unethical practice. Methods: This is a retrospective observational study. Among 200 patients who reported to Gynecology emergency with signs and symptoms suggestive of abortion process, those with history of abortion pill intake without prescription were included in the study group and their records were evaluated. Results: 70 patients who bought abortion pills over the counter were included in the study group. 90% (63/70) patients were not using any kind of contraceptive method. Only 55.71% (39/70) patients took the abortion pills as per the recommended standard protocol. Gestational age was < 8 weeks in 45.71% (32/70) patients only. Most common presenting complaint was varying amount of bleeding per vaginum followed by abdominal pain met in 97.14% (68/70) and 30% (21/70) patients respectively. 7.14% (5/70) patients presented to emergency in shock. Final diagnosis was complete abortion in 21.42% (15/70) patients, incomplete abortion in 47.14% (33/70), missed abortion in 11.42% ( 8/70), septic abortion in 7.14% ( 5/70) , threatened abortion in 5.71% ( 4/70), ectopic pregnancy in 5.71% ( 4/70) and molar pregnancy in 1.42% ( 1/70) patients and they were managed accordingly as per standard guidelines. Conclusion: The women in India should be aware of their legal right to safe abortion. They should stop buying the drug without prescription as medical abortion facilities are being made easily available, accessible and affordable to all. However strict ban on over the counter availability of abortion pills can make the situation worse.